2003
DOI: 10.1007/s00266-003-0108-8
|View full text |Cite
|
Sign up to set email alerts
|

Mild Degree of Poland?s Syndrome Reconstruction with Customized Silicone Prosthesis

Abstract: Poland's Syndrome consists of unilateral absence of the pectoralis major muscle, ipsilateral symbrachydaktylia, and occasionally associated other malformations of the anterior chest wall and breast. Mild Poland's Syndrome is characterized by asymmetry of the breasts with partial absence of the pectoralis major muscle. This report describes a 19-year-old man with unilateral hypoplasia of the breast, absence of the anterior axillary fold, and absence of the pectoralis major muscle. The patient's chest wall was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 18 publications
0
8
0
3
Order By: Relevance
“…4,7,13,15 However potential problems include seroma formation 4 and implant displacement. 13 Advantages of the implant only reconstructions include simplicity and fast recovery.…”
Section: Discussionmentioning
confidence: 99%
“…4,7,13,15 However potential problems include seroma formation 4 and implant displacement. 13 Advantages of the implant only reconstructions include simplicity and fast recovery.…”
Section: Discussionmentioning
confidence: 99%
“…4 In mild forms (especially non-associated with hand deformity) diagnosis can be overlooked. 5 These patient are generally diagnosed during radiologic screening test accidentally or when patients applied to a doctor for cosmetic purposes. It was shown that this malformation is associated with metabolic disorders, malignancies and organ anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Por su baja capacidad, la fosa posterior de los pacientes con MCHI sería insuficiente para contener al tallo cerebral y al cerebelo, deformándolo y promoviendo la herniación de las amígdalas cerebelosas a través del fora- men magnum 17,19,23 . El SP ha sido catalogado clásicamente como la asociación de una deficiencia del músculo pectoral aunada a deformidades del miembro superior ipsilateral; sin embargo, actualmente se reconoce que las alteraciones aisladas del músculo pectoral también entran dentro del espectro del síndrome 1,10,11 . Con base en las manifestaciones clínicas, el SP puede ser clasificado en tres grupos: 1.…”
Section: Discussionunclassified